Effects of copper on the leaf morpho-anatomy of Rhizophora mucronata: Implications for mangrove ecosystem restoration - KERSTIN LEI DJ. PEREZ; MARILYN O. QUIMADO; LERMA SJ. MALDIA; CRUSTY E. TINIO; JONATHAN O. HERNANDEZ; MARILYN S. COMBALICER (Society for Indonesian Biodiversity, 2021)
Abstract. Perez KLDJ, Quimado MO, Maldia MLSJ, Tinio CE, Hernandez JO, Combalicer MS. 2021. Effects of copper on the leaf morpho-anatomy of  Rhizophora mucronata: Implications for mangrove ecosystem restoration. Biodiversitas 22: 2058-2065. Mangrove is one of the important yet threatened ecosystems in the Philippines. One of the reported causes of its destruction is heavy-metal pollution. Forest restoration managers recommend species that exhibit functional and adaptive traits in their leaf morpho-anatomy to restore degraded mangrove ecosystem’s ecological integrity. In this study, the morphological and leaf anatomical characteristics of Rhizophora mucronata Lam. growing in mangrove sites in Mamburao, Occidental Mindoro, Philippines with different concentrations of copper element in the soil were examined to determine the species’ adaptation in copper exposed soil and its potential for mangrove ecosystem restoration. Leaf area was measured and leaf anatomical characteristics were determined through histological paraffin technique. The average leaf area of R. mucronata in the copper-rich site was relatively smaller than in site with considerably less copper. Further, anatomical characteristics in the copper-rich site such as thicker cuticular, upper epidermis, and hypodermal layers, thin mesophyll layers and vascular bundle, smaller and fewer xylary elements, and larger salt secretion cells indicate functional and adaptive traits. These structures may help R. mucronata tolerate the high concentration of heavy metals in the plant body and soil, suggesting its potential for mangrove ecosystem restoration especially in copper-polluted sites in the Philippines.